Abscisic Acid Regulates Auxin Homeostasis in Rice Root Tips to Promote Root Hair Elongation - Wang, Tao; Li, Chengxiang; Wu, Zhihua; Jia, Yancui; Wang, Hong; Sun, Shiyong; Mao, Chuanzao; Wang, Xuelu (Frontiers in Plant Science, 2017)
Abscisic acid (ABA) plays an essential role in root hair elongation in plants, but the regulatory mechanism remains to be elucidated. In this study, we found that exogenous ABA can promote rice root hair elongation. Transgenic rice overexpressing SAPK10 (Stress/ABA-activated protein kinase 10) had longer root hairs; rice plants overexpressing OsABIL2 (OsABI-Like 2) had attenuated ABA signaling and shorter root hairs, suggesting that the effect of ABA on root hair elongation depends on the conserved PYR/PP2C/SnRK2 ABA signaling module. Treatment of the DR5-GUS and OsPIN-GUS lines with ABA and an auxin efflux inhibitor showed that ABA-induced root hair elongation depends on polar auxin transport. To examine the transcriptional response to ABA, we divided rice root tips into three regions: short root hair, long root hair and root tip zones; and conducted RNA-seq analysis with or without ABA treatment. Examination of genes involved in auxin transport, biosynthesis and signaling indicated that ABA promotes auxin biosynthesis and polar auxin transport in the root tip, which may lead to auxin accumulation in the long root hair zone. Our findings shed light on how ABA regulates root hair elongation through crosstalk with auxin biosynthesis and transport to orchestrate plant development.